If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -52 = 2x + 14 Reorder the terms: -52 + 8x = 2x + 14 Reorder the terms: -52 + 8x = 14 + 2x Solving -52 + 8x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -52 + 8x + -2x = 14 + 2x + -2x Combine like terms: 8x + -2x = 6x -52 + 6x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 -52 + 6x = 14 + 0 -52 + 6x = 14 Add '52' to each side of the equation. -52 + 52 + 6x = 14 + 52 Combine like terms: -52 + 52 = 0 0 + 6x = 14 + 52 6x = 14 + 52 Combine like terms: 14 + 52 = 66 6x = 66 Divide each side by '6'. x = 11 Simplifying x = 11
| x^2-72x+256=0 | | 180=108(x+18) | | (12+8x)=1 | | (7+3i)-(2+3i)= | | 3y+3x-2=7 | | 1n+9n-10-3= | | 7(9x-3)=4(3x+2) | | 148-4x=60 | | (12-8x)=1 | | 4x-18+x^2-7x=10 | | 7(x+11)=18x+22 | | -2(d+4)-d-3=-3(d+5)+4 | | (5-i)(5+i)= | | -3.2(30)=-96 | | x^2-4x+1=k(x-4) | | x+2y+2z=-1 | | 3m-42-12+12=24 | | 3x+21=5 | | 7(n-8)-(6-n)= | | (3-i)+(1-2i)= | | 9x+12=15x-24 | | v/8=14 | | 95-7x=60 | | 5+5=10+10x | | 10(4-3i)= | | -3.2a=-96 | | 7y-168=3y | | 81r-48rt=0 | | 2a^2+11a=-5 | | w/12=9 | | 0.4(3x-15)=0 | | 95-7x+3x+21=95 |